1991
DOI: 10.1210/endo-129-2-1075
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-II Receptor Subtypes in Fetal Tissues of the Rat: Autoradiography, Guanine Nucleotide Sensitivity, and Association with Phosphoinositide Hydrolysis

Abstract: Quantitative autoradiography revealed large numbers of angiotensin-II (AT) receptors in the 18-day-old rat embryo. The selective AT-1 antagonist DuP 753 readily competed for AT receptors in liver, lung parenchyma, and choroid plexus, and these receptors are classified as AT-1 receptors. The selective AT-2 displacers CGP 42112 A and/or PD 123177 competed with high affinity with AT bound to most receptors located in skeletal muscle, skin, diaphragm, bronchi, and stomach, and these receptors are classified as AT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(54 citation statements)
references
References 25 publications
4
50
0
Order By: Relevance
“…The highly abundant expression of AT 2 receptor during embryonic and neonatal growth, the rapid disappearance after birth (4,6), and the up-regulation of AT 2 receptor in myocardial infarction (27), cardiac hypertrophy (28), and skin wound (29) suggest that this receptor is closely involved with growth, development, and/or differentiation. Dudley et al (14) reported that the addition of growth factors, such as basic fibroblast growth factor or serum, to quiescent R3T3 cells caused a rapid decrease in the number of surface AT 2 receptor sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highly abundant expression of AT 2 receptor during embryonic and neonatal growth, the rapid disappearance after birth (4,6), and the up-regulation of AT 2 receptor in myocardial infarction (27), cardiac hypertrophy (28), and skin wound (29) suggest that this receptor is closely involved with growth, development, and/or differentiation. Dudley et al (14) reported that the addition of growth factors, such as basic fibroblast growth factor or serum, to quiescent R3T3 cells caused a rapid decrease in the number of surface AT 2 receptor sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a second receptor subtype known as AT 2 receptor has been cloned by us and others (1,2). The AT 2 receptor is abundantly and widely expressed in fetal tissues, but present only in at limited levels in adult tissues such as adrenal medulla, specific brain regions, uterine myometrium, heart, and atretic ovarian follicles (3)(4)(5)(6)(7)(8). The highly abundant expression of this receptor during embryonic and neonatal growth and quick disappearance after birth has led to the suggestion that this receptor is involved in growth, development, and/or differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of ANG II receptors are of the AT2 subtype during gestation (Grady et al 1991 ;Tsutsumi et al 1991 ;Feuillan et al 1993) and are expressed in many tissues such as undifferentiated mesenchyme which are not ANG II target tissues in the adult (Grady et al 1991). In order to determine the role of the AT1 and AT2 receptor subtypes during organogenesis, embryos were cultured in the presence of GR117289 (AT1 blocker) and PD123319 (AT2 blocker).…”
Section: mentioning
confidence: 99%
“…In these novel areas binding was shown rapidly to decrease within 1 d of birth . Subsequent investigation using receptor subtype specific antagonists has demonstrated that the majority of fetal ANG II binding sites are AT2 receptors (Grady et al 1991 ;Tsutsumi et al 1991 ;Feuillan et al 1993) which are expressed transiently in the skin, skeletal muscle and in undifferentiated mesenchyme during gestation (Grady et al 1991). Such abundant but transient expression of the AT2 receptor has led to the hypothesis that ANG II may regulate growth during embryonic and fetal development.…”
mentioning
confidence: 99%